Determinants of gold ownership among households in Indonesia: The role of economic activity across provinces - Aditya Idris (EcoProfit: Sustainable and Environment Business, 2026)
Background: Gold has long remained a key financial asset, despite increasing financial inclusion and economic modernization, household gold ownership in Indonesia persists across regions. Existing studies emphasize income and macroeconomic conditions but often fail to capture real economic dynamics at the regional level. This study aims to examine the relationship between regional economic activity and household gold ownership in Indonesia, with particular attention to heterogeneity across regions with different levels of gold ownership. Methods: This study employs provincial-level panel data for 34 Indonesian provinces covering the period 2014-2024. Economic activity is measured using a combination of satellite-based Night-time Lights and gross regional domestic product per capita. The analysis applies a moment quantile regression framework to capture distributional heterogeneity in household gold wonership, while controlling for demographic and structural factors. Findings: The results reveal that economic activity has a heterogeneous effect on household gold ownership across quantiles. Night-time lights exhibit a positive and statistically significant association with gold ownership at lower quantiles, indicating that increased real economic activity supports initial gold accumulation in regions with low ownership levels. Gross regional domestic product per capita shows a consistently positive and significant relationship, highlighting the dominant role of formal income capacity in sustaining higher levels of gold ownership. Conclusion: The study concludes that household gold ownership in Indonesia is shaped by multidimensional economis activity and exhibits strong regional heterogeneity. These findings underscore the importance of distribution-sensitive analysis in understanding household financial behavior and offer policy-relevant insights for the development of gold-based financial services. Novelty/Originality of this article: This study contributes novel empirical evidence by integrating satellite-based economic activity measures with conventional income indicators and applying a quantile-based panel approach to analyze household gold ownership.